Biaya Pelayanan, Dukungan Suami dan Rasa Takut Terhadap Penggunaan Metode Kontrasepsi Jangka Panjang: Service Fees, Husband's Support and Fear of Using Long-Term Contraceptive Methods - Ari Salis Saputri (Open Access Jakarta Journal of Health Sciences, 2022)
Introduction: The coverage of MKJP were 6.99% (implants), 7.15% (IUD), 2.78% (MOW), and 0.53% (MOP) indicating the use of MKJP contraceptive methods in Indonesia decreased from the previous year (RI Ministry of Health, 2018). The low use of MKJP has been a cause of stagnation in birth rates over the past decade. The purpose of this study was to determine the relationship between service costs, husband support and fear of action against the use of long-term contraception methods at the Umi Rahma Clinic in Bekasi in 2019 Method: Using descriptive analytic design with Cross Sectional approach. The study population was all EFA women who performed family planning at the Umi Rahma Clinic in Bekasi in 2019, a sample of 50 respondents using the Accidental Sampling technique using a questionnaire. This study uses univariate and bivariate analysis with Chi-Square statistical tests Result: . Chi-Square statistical test results service costs for the use of MKJP obtained P-Value 0.002, support for the husband of the use of MKJP obtained P-Value 0.001, fear action against the use of MKJP obtained P-Value 0.001. Discussio: Long-Term Contraception Methods, because costs greatly affect all actions that will be taken by couples of childbearing age, one of which is in the selection or decision-making on the use of contraceptive methods. Conclusion: Concluded that there is a relationship between service costs , husband support and fear of action towards the use of MKJP